Mather sets for sequences of matrices and applications to the study of joint spectral radii. Issue 1 (16th January 2013) - Morris, Ian D.
Abstract : The joint spectral radius of a compact set of d × d matrices is defined to be the maximum possible exponential growth rate of products of matrices drawn from that set. In this article, we investigate the ergodic‐theoretic structure of those sequences of matrices drawn from a given set whose products grow at the maximum possible rate. This leads to a notion of Mather set for matrix sequences, which is analogous to the Mather set in Lagrangian dynamics. We prove a structure theorem establishing the general properties of these Mather sets and describing the extent to which they characterise matrix sequences of maximum growth. We give applications of this theorem to the study of joint spectral radii and to the stability theory of discrete linear inclusions. These results rest on some general theorems on the structure of orbits of maximum growth for subadditive observations of dynamical systems, including an extension of the semiuniform subadditive ergodic theorem of Schreiber, Sturman and Stark, and an extension of a noted lemma of Y. Peres. These theorems are presented in the appendix.